Towards a Cashless Transactional Society Through the Adoption of Digital Banking Services - Ngandu, Matipa Ricky; Mwansa, Gardner; Ntoyabo, Siwongiwe Queenest (The Indonesian Journal of Computer Science, 2025)
This study explores the adoption of digital banking services in a rural South African town in the Eastern Cape, emphasizing its contribution to a cashless society. Employing a quantitative method, it examines digital banking usage, adoption challenges, and information security awareness. Data were collected through surveys and analyzed using descriptive statistics. Findings show that mobile and online banking are widely used for convenience and accessibility, with most users engaging in money transfers, credit payments, and online shopping. However, challenges such as poor digital literacy, infrastructure issues like internet access, cost of access, and cybersecurity concerns persist. Users face risks like phishing, hacking, and social engineering, revealing gaps in security awareness and trust. These issues particularly affect older users and those with limited technological experience. While digital banking improves financial inclusion and economic engagement in rural areas, its full potential is hindered by these barriers. The study underscores the need for digital literacy programmes, infrastructure improvements, and robust cybersecurity measures to build trust and ensure secure adoption. Future research should evaluate interventions, explore emerging technologies like blockchain and AI, and compare regional strategies for inclusive digital financial systems.